Bacterial Probiotics Induce an Immune Response in the Honey Bee (Hymenoptera: Apidae) - Evans, J.D.; Lopez, D.L.
To explore immune systemactivationinthe honey bee,Apis melliferaL., larvae of four ageswere exposed through feeding to spores of a natural pathogen, Paenibacillus larvae larvae, to cells of adiverseset of relatednonpathogenicbacteria, andtobacterial coat components.These larvaewere then assayed for RNA levels of genes encoding two antibacterial peptides, abaecin and defensin. Larvae exposed to eitherP. l. larvaeor a mix of nonpathogenic bacteria showed high RNA levels for the abaecin gene relative to controls. First instars responded signiÞcantly to the presence of the nonpathogenicmixwithin12hafter exposure, a timewhen they remainhighly susceptible tobacterial invasion. This response was sustained for two successive instars, eventually becoming 21-fold higher in larvae exposed to probiotic spores versus control larvae. The mixture of nonpathogenic bacteria is thereforepresented as a potential surrogate for assaying the immune responses of different honeybee lineages. It also is proposed that nonpathogenic bacteria can be used as a probiotic to enhance honey bee immunity, helping bee larvae, and other life stages, survive attacks from pathogens in the field.
Keywords: INNATE IMMUNITY; ANTIMICROBIAL PEPTIDE; AMERICAN FOULBROOD